Formalization of Matrix Theory in HOL4 - Zhiping Shi; Yan Zhang; Zhenke Liu; Xinan Kang; Yong Guan; Jie Zhang; Xiaoyu Song (Advances in Mechanical Engineering, 2014)
Matrix theory plays an important role in modeling linear systems in engineering and science. To model and analyze the intricate behavior of complex systems, it is imperative to formalize matrix theory in a metalogic setting. This paper presents the higher-order logic (HOL) formalization of the vector space and matrix theory in the HOL4 theorem proving system. Formalized theories include formal definitions of real vectors and matrices, algebraic properties, and determinants, which are verified in HOL4. Two case studies, modeling and verifying composite two-port networks and state transfer equations, are presented to demonstrate the applicability and effectiveness of our work.